Antioxidant role of Nymphaea alba flower extract against alloxan induced experimental diabetes condition. - G. KARTHIKEYAN; S. RAJARAM; S. ARULRAJA (International Journal of Pharma and Bio Sciences, 2019)
Alloxan could be used to experimentally induce diabetes and has been successfully induced in a variety of experimental animals. The current investigation was aimed to investigate the anti-diabetic activity of Nymphaea alba flower extract against alloxan induced diabetic condition in experimental rats. N.alba flower extract was orally given to diabetic animals at various concentration. There are numerous pharmacologically and bioactive significant components which have been attained from Nymphaea alba. Treatment of N.alba flower extract significantly (p < 0.05) lowered the level of serum glucose, HbA1C, total bilirubin, malondialdehyde levels in experimentally induced diabetic animals in a concentration dependent fashion. In earlier studies the ethanolic flower extract from Nymphaea alba was investigated for hepatoprotective activity by carbon tetra chloride and paracetamol induced hepatotoxicity in experimental rats. In alloxan treated animals, significant (p < 0.05) reduction in the levels of antioxidant enzymes such as glutathione peroxidase (Gpx), glutathione S transferase (GST), catalase (CAT) and superoxide dismutase (SOD), nitric oxide (NO) and glutathione were observed. The deterioration in the activities of the enzymes in alloxan-induced diabetic animals and accomplishment of near normality in diabetic induced and N.alba plant extracts treated groups were also being investigated in the present study. Treatment with N.alba flower extract could revert back the antioxidant enzyme levels to normal in a dose dependent manner (p < 0.05). The present investigation revealed that N.alba flower extract exerted strong antidiabetic action by bringing back the antioxidant system and anti-hyperglycemic action. In this study the flower extract of Nymphaea alba showed favorable beneficial properties of prevention as well as treatment of diabetes.